1986
DOI: 10.1042/bj2390711
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of the third component of complement (C3) by the human monocytic-cell line U-937 Induction by phorbol myristate acetate

Abstract: Phorbol myristate acetate (PMA)-stimulated human monocyte-like cells (U-937) were found to synthesize the third component of complement (C3), as shown by enzyme-linked immunosorbent assay and immunoprecipitation from [35S]methionine-labelled culture supernatants. C3 synthesis occurred at a rate of about 160 ng of C3/24 h per 10(6) cells on day 7 after addition of PMA; it was blocked by cycloheximide treatment and was restored after removal of the inhibitor. SDS/polyacrylamide-gel-electrophoretic analysis of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1988
1988
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 38 publications
(46 reference statements)
1
7
0
Order By: Relevance
“…However, after 24 h of incubation the proportion of intact C3 was lower than after 2 h (results not shown). This is in agreement with the results of Bengio et al [10], who observed that the haemolytic activity of U937-derived C3 decreased after 6 h in culture due to proteolysis.…”
Section: Modulation Of Synthesis and Phosphorylation Of C3 In Vitrosupporting
confidence: 93%
See 2 more Smart Citations
“…However, after 24 h of incubation the proportion of intact C3 was lower than after 2 h (results not shown). This is in agreement with the results of Bengio et al [10], who observed that the haemolytic activity of U937-derived C3 decreased after 6 h in culture due to proteolysis.…”
Section: Modulation Of Synthesis and Phosphorylation Of C3 In Vitrosupporting
confidence: 93%
“…Complement components are mostly synthesized in hepatocytes [1][2][3][4], but substantial amounts are also secreted by monocytes\macrophages [5][6][7] ; local synthesis of complement proteins by macrophages plays an important role in the inflammatory response [8]. The human monocytic cell line U937 [9] is a suitable model for complement synthesis in monocytes\ macrophages, and has been reported to synthesize a number of components, including C3 [10], C4 [11], Factor B [12] and Factor H [13]. The secretion of C3 by U937 is stimulated by, e.g., PMA, [10,14], lipopolysaccharide (LPS), and interferon-γ [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown by several groups that activation of M ¤ enhances C3 production, and locally produced C3 is known to influence several cellular responses [14][15][16][17][18][19]. We found that M ¤ cultured on immobilized C1q and MBL also produced increased amounts of C3 (measured by ELISA) and C1q proved to be a more potent activator (data not shown).…”
Section: Self Opsonization By C3 Derived From C1qand Mbl-stimulated M Dmentioning
confidence: 55%
“…Thccostimulaiory effect of certain IgG isotypes and lL-6 on C3 biosynthesis by macrophages, and the actual expression and availability of FcvRs, may have an important role in local immune responses. All the more since C3 produced by macrophages has been demonstrated to be cleaved by cell surface proteases, to bind covalently to the C3-producing cell [16,21,22] and to modulate various FcyR-dependent functions [22]. In addition.…”
Section: Discussionmentioning
confidence: 99%